Capturing The Benefit of Monsoonal and Tropical Climate to Enhance National Food Security - Istiqlal Amien; Eleonora Runtunuwu (Jurnal Penelitian dan Pengembangan Pertanian, 2010)
Although the consumption level is declining with improved economy and living condition, rice remains the staple food in many Asian countries. With annual consumption per capita of more than 100 kg, Indonesia is far higher than Japan, Korea, Taiwan, and Malaysia with around 90 kg but less than the least developed countries in Southeast Asia, Laos and Myanmar that consume around 200 kg. Java the most populous island with about 7% of Indonesian terrestrial territory has long been and is still the national rice basket although its contribution to the national rice production is steadily declining. With population is still growing by 1.30% annually, competition for food, water, and energy will increase. Consequently food prices will rise, more people will go hungry, and migrants will flee theworst-affected regions. Therefore, to cater the national rice demand, alternatives has to be found in outer islands. The geographic position and variable climate of monsoonal and tropical rainfall patterns as well as the availabilityof large swathes of swampy land offer opportunity to evenly spread planting time and hence rice production throughout the year. However, recent rapid development of tree plantations will make it difficult to implement without political will supported with strong policy and appropriate planning. This paper describes the challenges and opportunities in utilizing climate variability to enhance national food security and improve farmers’ welfare.